Penerapan Pembelajaran Tematik Terpadu Era Daring di Madrasah Ibtidaiyah - Yuliana Susanti (AS-SABIQUN, 2021)
This study aims to describe the planning, implementation, assessment, barriers, efforts, and the impact of integrated thematic learning at MI Birrul Walidain NW Rensing and MI NW Bungtiang 2. The study used qualitative descriptive. Data collection techniques using observation, interviews, and document studies. The results of the study (1) planning, the teacher makes RPP according to the 2013 Curriculum component, (2) implementation, the teacher combines KD in subjects (thematics) through a scientific approach, (3) assessment, includes knowledge, attitudes, and skills, (4) barriers , time allocation for making lesson plans, learning variations, questioning activities, infrastructure and assessment facilities are still lacking, (5) efforts, teachers prepare lesson plans, learning variations, using media and the surrounding environment, (6) the impact of knowledge, skills and student attitudes is still quite good because students are not familiar with the online learning system.